A Non-Invasive Method for Detection of Antihypertensive Drugs in Biological Fluids: The Salivary Therapeutic Drug Monitoring - Avataneo, Valeria; Fanelli, Elvira; De Nicolò, Amedeo; Rabbia, Franco; Palermiti, Alice; Pappaccogli, Marco; Cusato, Jessica; De Rosa, Francesco Giuseppe; D'Avolio, Antonio; Veglio, Franco (Frontiers in Pharmacology, 2022)
Objectives. Arterial hypertension is still the most frequent cause of cardiovascular and cerebrovascular morbidity and mortality. Antihypertensive treatment has proved effective in reduction of cardiovascular risk. Nevertheless, lifestyle interventions and pharmacological therapy in some cases are ineffective in reaching blood pressure target values, despite full dose and poly-pharmacological treatment. Poor adherence to medications is an important cause of treatment failure. Different methods to assess therapeutic adherence are currently available: Therapeutic Drug Monitoring in biological fluids has previously demonstrated its efficacy and reliability. Plasma and urine have been already used for this purpose, but they may be affected by some practical limitations. Saliva may represent a feasible alternative. Methods. Fourteen antihypertensive drugs and 2 metabolites were simultaneously tested in plasma, urine and saliva. Tested molecules included: atenolol, nebivolol, clonidine, ramipril, olmesartan, telmisartan, valsartan, amlodipine, nifedipine, doxazosin, chlorthalidone, hydrochlorothiazide, indapamide, sacubitril, ramiprilat and sacubitrilat. Therapeutic Drug Monitoring was performed using ultra-high performance liquid chromatography, coupled to tandem mass spectrometry (UHPLC-MS/MS). The method has been preliminary evaluated in a cohort of hypertensive patients. Results. The method has been validated according to FDA and EMA guidelines. The application on a cohort of 32 hypertensive patients has demonstrated sensibility and specificity of 98% and 98.1% respectively, with a good feasibility in real life clinical practice. Conclusions. Saliva may represent a feasible biological sample for Therapeutic Drug Monitoring, by non-invasive collection, prompt availability and potential accessibility also in out-of-clinic settings.